1977
DOI: 10.1177/030631277700700205
|View full text |Cite
|
Sign up to set email alerts
|

Co-Citation Analyses of Science: An Evaluation

Abstract: For the past several years, Henry Small and collaboratorsl have been arguing strongly on behalf of the utility of a technique called 'co-citation analysis' as a tool for understanding the specialty structure of science. Data which we have collected over the past two years on a specialty in elementary particle physics, the study of weak interactions,2 allow an evaluation of co-citation analysis, and we report the results in this Note.A series of claims for the technique of co-citation analysis have been made by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…The largest of the resulting fragments from the break-up of the prior dominant group is a cluster of eight papers dealing almost exclusively with n-type semiconductors, with papers originating primarily from two research labs. Such short-term disruptions have been observed in prior co-citation studies [SULLIVAN & AL., 1977;SMALL, 1977].…”
Section: Cluster Evolution 2004-2007supporting
confidence: 66%
“…The largest of the resulting fragments from the break-up of the prior dominant group is a cluster of eight papers dealing almost exclusively with n-type semiconductors, with papers originating primarily from two research labs. Such short-term disruptions have been observed in prior co-citation studies [SULLIVAN & AL., 1977;SMALL, 1977].…”
Section: Cluster Evolution 2004-2007supporting
confidence: 66%
“…For example, Small (1977) found that immediacy rose during a 'mini-revolution' in Collagen research. Sullivan, White and Barboni (1977) demonstrated a similar phenomenon during a period of rapid theory change in the physics of weak interactions. Dean (1980) found that psychologists generally cited papers about seven years old: however, this dropped sharply during the period when additivity theory was displacing inhibitory theory äs the dominant explanation for the probability of a conditioned response.…”
Section: Patterns Of Scholarly Communication In Information Policymentioning
confidence: 67%
“…The question has been raised whether in this way the entire specialty, or only a subgroup of publications of the specialty is identified (e.g., Sullivan et al, 1977). Small, who introduced the co-citation technique (Small, 1973), claims that the citing authors of a cluster constitute a highly relevant subgroup of the current practioners of a specialty (Small, 1977).…”
Section: Introductionmentioning
confidence: 99%